Call recognition and female choice in a treefrog with a multicomponent call. (11th April 2018) - Oliva, Mark V.; Kaiser, Kristine; Robertson, Jeanne M.; Gray, David A.
Abstract: Acoustic mating signals are typically species‐specific, and often additionally are subject to directional female preferences. Male executioner treefrogs, Dendropsophus carnifex, produce a multicomponent advertisement call composed of an introductory screech note followed by two or more click notes. Here, we tested (i) call recognition by comparing female directed phonotaxis towards individual and combined call components: screech vs. clicks vs. screech + clicks, (ii) female preferences for greater numbers of click notes and (iii) female preferences for faster call rates. The results demonstrated that screeches and clicks, presented either separately or together as a complete call, evoke similar female responses, suggesting that either note was sufficient to elicit a mate‐recognition response. Additionally, females preferred calls with greater numbers of click notes and with faster call rates. We interpret these results within the context of female mate selection in natural choruses.